髋关节试验机四自由度并联模块运动学与动力学特性分析 - 成钰龙; 程刚; 贾丹; 张峰 (Jixie chuandong)
The accuracy of the test results of friction and wear characteristics of artificial hip joint materials is decided by the accurate movement of test equipment.Due to that,3SPS +1PS parallel mechanism is selected as the core of the parallel module of bionic hip simulator.The solid model is established by using Pro/E and ADAMS.According to the bionic features of kinematic and dynamic characteristics of normal human hip,we can run their kinematic and dynamic simulation in ADAMS.Then it is concluded that the main movements of every limb of the parallel mechanism lie in the Z direction.The curve of r2 is the most complex,but its displacement,velocity,acceleration amplitude is relatively minimal.The displacement curve of r1 is the largest.From the force curve of constraint joints,it is found that the major forces in the parallel mechanism resulted by the external force lie in the Z-direction of r0 and r01.The simulation results lay the foundation for analyzing of error sensitivity of structure,designing corresponding control system and the parallel mechanical structure.